A Cross-Sectional Examination of the Association Between Dyspnea and Distress as Experienced by Palliative Home Care Clients and Their Informal Caregivers. Issue 1 (2nd April 2016) - Freeman, Shannon; Hirdes, John P.; Stolee, Paul; Garcia, John
ABSTRACT: This study examined the association between dyspnea and distress as experienced by both palliative home care clients and their informal caregivers as a unit of care. Cross-sectional analysis was conducted using the interRAI Palliative Care Assessment database. Responses from 6, 655 individual palliative home care clients across six regional jurisdictions in Ontario, Canada were included. This study found that clients experiencing dyspnea were more likely to show overall signs of distress; report one or more signs of self-reported distress; and be at risk for depression when compared to clients who do not experience dyspnea. Caregivers of clients experiencing dyspnea were more likely to exhibit distress than caregivers of clients not reporting dyspnea. When indicators of caregiver distress and client distress were combined, 53% of the caregiver-client units exhibited distress. Social work practitioners should include a focus on distress within the care unit as a priority when care planning to meet the needs of persons nearing the end of life. Members of the care team should consider available treatment and management options tailored to meet both the client and their informal caregiver's needs.